Dalihan Na Tolu Culture and Islamic Education: Traditional and Religious Collaboration in Shaping Character - Pulungan, Muhammad Yusuf (Pascasarjana Universitas KH. Abdul Chalim, 2025)
This research aims to examine the collaboration between the local culture of Dalihan Na Tolu and Islamic education in the formation of adolescent character in the Mandailing community. This study is motivated by the urgency of character education, which not only relies on the formal system based on religion but also utilizes the power of local cultural values as an authentic source of informal education. This study uses a qualitative method with a sociology of education approach. Data were obtained through interviews with traditional leaders, religious leaders, Islamic education teachers, and adolescents, participatory observation of Islamic traditional practices and educational activities, and analysis of cultural and religious documents. The results of the study show that the milieu has a vital role in shaping the character of adolescents. Cultural and religious collaboration is reflected in local Islamic traditions, local Islamic educational institutions, and conflict resolution mechanisms. This research provides the basis for the formulation of inclusive education policies based on local wisdom. The implication is that integrating local culture and Islamic education can enhance the effectiveness of character education, serve as an alternative model, and cultivate a young generation with character, tolerance, and competitiveness.